Composite material bracket, preparation method and application thereof

By coating the active coating of natural biomaterials on the synthetic biomaterial scaffold, the problems of poor hydrophilicity and insufficient mechanical properties of biomaterial scaffolds in the prior art are solved, and better cell interaction and cartilage repair effects are achieved.

CN119746163APending Publication Date: 2025-04-04NOVAPRINT THERAPEUTICS SUZHOU CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411963778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, biomaterial scaffolds used for cartilage tissue repair have problems such as poor hydrophilicity, lack of cell recognition signals, low surfactivity and insufficient mechanical properties.

Method used

Using the design of composite material scaffolds, the composite material scaffolds with bioactive surfaces are formed by coating the active coating formed by natural biomaterials on the scaffold body formed by synthetic biological materials. Combining the advantages of both, a composite material scaffold with a bioactive surface is formed.

Benefits of technology

The scaffold surfactivity and mechanical properties are enhanced, which promotes cell adhesion, proliferation and differentiation, and improves the repair effect of cartilage tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746163A_ABST
    Figure CN119746163A_ABST
Patent Text Reader

Abstract

The present invention discloses a composite material stent, a preparation method and application thereof, and relates to the technical field of biomaterials and tissue engineering. The composite material stent provided by the present invention comprises a stent body formed of synthetic biomaterials, and an active coating formed of natural biomaterials is coated on the stent body to form a composite material stent with a bioactive surface, which has better surface activity than pure synthetic material stents, and better mechanical properties than pure natural materials, and has very good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials and tissue engineering, and in particular to a composite material scaffold, a preparation method and application thereof. Background Art

[0002] Cartilage tissue has no blood vessels and limited repair capacity. Once damaged, it is difficult to self-repair. Among the various technologies for cartilage tissue repair, tissue engineering cartilage technology is one of the most promising technologies for repairing cartilage damage. Tissue engineering relies on the use of biomaterial scaffolds to support cell proliferation, migration and differentiation. Scaffolds, seed cells and growth factors are the three core elements of tissue engineering. Biomaterial scaffolds can provide a spatial framework for chondrocytes to grow and attach, and can also serve as a carrier of growth factors, provide physical and mechanical stimulation and biochemical factor stimulation, coordinate the interaction between bioactive factors and cells, and affect the expression of cell surface factor receptors and cell differentiation, thereby promoting the repair of cartilage tissue.

[0003] The conditions that an ideal biomaterial scaffold should have include: (1) good biocompatibility, non-toxicity, and conducive to cell survival and proliferation; (2) a three-dimensional porous structure that is conducive to cell growth and migration, provides sufficient space for regenerated tissue, and facilitates the transport of nutrients and metabolites; (3) can provide a certain mechanical strength and mechanical support, and can still maintain a certain shape for a certain period of time after implantation in the body, so that the new tissue can form the desired appearance; (4) effective surface activity, which is conducive to cell adhesion, can activate cell-specific gene expression, and maintain normal cell phenotype; (5) suitable biodegradability, and the degradation rate matches the tissue regeneration rate.

[0004] Currently, the materials that can be used for cartilage tissue engineering scaffolds mainly include two categories: artificial synthetic biomaterials and natural biomaterials:

[0005] Synthetic biomaterials mainly include degradable polyester materials such as polycaprolactone, polylactic acid, polyglycolic acid, and polytrimethylene carbonate. These biomaterials generally have certain mechanical properties and good biocompatibility. Their composition, molecular weight, and surface microstructure are easy to design and control, and they are easy to process. They can be prepared into three-dimensional porous scaffolds through 3D printing. However, these biomaterials have the disadvantages of poor hydrophilicity, lack of functional groups that cells can recognize and bind growth factors, low surface activity, and poor cell affinity and adhesion.

[0006] Natural biomaterials mainly include collagen (type I or type II), fibrin, gelatin, silk protein, glycosaminoglycans (hyaluronic acid, chondroitin sulfate), alginate, chitosan, etc. Natural biomaterials have good biocompatibility, similar composition to cartilage matrix, good hydrophilicity, cell recognition signals (such as certain amino acid sequences) or active groups, which are conducive to cell adhesion and maintenance of cell differentiation, but have defects such as low mechanical properties, rapid degradation and absorption, difficult to control purity, and difficult processing.

[0007] Therefore, there is an urgent need to develop scaffolds with bioactive surfaces that also have good mechanical properties for easy processing.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a composite material scaffold, a preparation method and application thereof, which has a bioactive surface and also has good mechanical properties.

[0010] The present invention is achieved in that:

[0011] In a first aspect, the present invention provides a composite material stent, comprising a stent body formed of a synthetic biomaterial, and an active coating formed of a natural biomaterial coated on the stent body.

[0012] In an alternative embodiment, the synthetic biomaterial is selected from at least one of polycaprolactone, polylactic acid, polyglycolic acid, polytrimethylene carbonate, polylactic acid-glycolic acid copolymer, polylactic acid-caprolactone copolymer and polylactic acid-trimethylene copolymer;

[0013] And / or, the natural biomaterial is selected from at least one of sodium hyaluronate, chondroitin sulfate, sodium alginate, chitosan, collagen, fibrin, silk fibroin and gelatin.

[0014] In an optional embodiment, the stent body has a three-dimensional through-pore structure;

[0015] Preferably, the stent body is prepared by a melt extrusion additive manufacturing method, and is composed of melt-extruded fiber filaments of synthetic biomaterials arranged in parallel and stacked layer by layer at different angles; wherein the fiber filament spacing is 370μm-1000μm, the fiber filament diameter is 200μm-500μm, and the porosity of the stent body is 65%-83%.

[0016] In an optional embodiment, the thickness of the active coating is 1.0 μm-5.0 μm, and the mass fraction of the active coating in the composite material stent is 1.0%-5.0%.

[0017] In a second aspect, the present invention provides a method for preparing a composite material stent according to any one of the aforementioned embodiments, comprising: coating an active coating on a stent body.

[0018] In an optional embodiment, the method includes: firstly immersing the stent body in an alkaline solution to obtain a micro-nano structure, and then immersing the stent body in a natural biomaterial solution to form an active coating.

[0019] In an optional embodiment, the process of obtaining the micro-nano structure includes: immersing the stent body in an alkali solution with a concentration of 1 mol / L-10 mol / L for surface treatment, the treatment temperature is 25°C-45°C, and the treatment time is 12h-24h;

[0020] Preferably, the alkali solution is selected from at least one of an aqueous sodium hydroxide solution and an aqueous potassium hydroxide solution;

[0021] Preferably, after soaking in the alkali solution, the treated stent is washed with water and dried.

[0022] In an optional embodiment, the process of forming the active coating comprises: immersing the stent body having the micro-nano structure in a natural biomaterial solution under vacuum conditions for 10 min to 30 min, and then drying;

[0023] Preferably, the mass fraction of the natural biological material solution is 0.5%-1.5%, and the operating pressure during the immersion process is controlled to be -100KPa to 0KPa;

[0024] Preferably, after the immersion in the natural biomaterial solution is completed, the stent is placed on a hydrophobic platform for drying, and the drying temperature is controlled to be 30° C.-45° C., and the drying time is 12 h-72 h.

[0025] In an optional embodiment, the process of forming the active coating further comprises: after immersing in the natural biomaterial solution and drying, placing the stent containing the natural biomaterial coating in a crosslinking agent solution for a crosslinking reaction, and washing and drying after the reaction;

[0026] Preferably, the cross-linking agent used in the cross-linking agent solution is selected from at least one of glutaraldehyde, calcium chloride and EDC / NHS according to different natural materials.

[0027] In a third aspect, the present invention provides a use of any composite material scaffold in the aforementioned embodiments or a composite material scaffold prepared by any preparation method in the aforementioned embodiments in preparing a cartilage repair product;

[0028] Preferably, the cartilage is selected from at least one of articular cartilage, nasal cartilage and ear cartilage.

[0029] The present invention has the following beneficial effects: the composite material stent provided by the present invention comprises a stent body formed of synthetic biomaterials, and an active coating formed of natural biomaterials is coated on the stent body, thereby forming a composite material stent with a bioactive surface. The composite material stent has better surface activity than a pure synthetic material stent, and has better mechanical properties than pure natural materials, and has very good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a low-magnification SEM image of the micro-nano structure of the stent after surface treatment in Example 1;

[0032] Figure 2 This is a low-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 1;

[0033] Figure 3 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 1;

[0034] Figure 4 Fluorescence staining photos of live and dead cells after 3-day cell culture on the composite material scaffold prepared in Example 1; (A) represents live cell staining; (B) represents dead cell staining;

[0035] Figure 5 This is an Alcian blue staining image of the composite material scaffold prepared in Example 1 implanted into rabbit nasal cartilage for 6 months;

[0036] Figure 6 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 2;

[0037] Figure 7 This is an element distribution diagram of the cross-sectional area of ​​the coating on the composite material bracket of Example 2 tested by EDS;

[0038] Figure 8 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 3;

[0039] Fig. 9 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 4;

[0040] Fig.10 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 5;

[0041] Fig.11 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 6;

[0042] Fig.12 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 7;

[0043] Fig.13 This is a low-magnification SEM image of the composite material bracket prepared in Example 8;

[0044] Fig.14 This is a low-magnification SEM image of the composite material bracket prepared in Example 9;

[0045] Fig.15 The low-magnification SEM images of the cross-section of the fiber filaments on the composite material scaffold that failed to be prepared in Example 10, (A) is the fiber filaments not covered with the coating, and (B) is the fiber filaments partially covered with the coating;

[0046] Fig.16 This is an optical microscope photograph of a composite material bracket that failed to be prepared in Example 11;

[0047] Fig.17 This is an optical microscope photo of the composite material bracket that failed to be prepared in Example 12;

[0048] Fig.18 Photos of the stent solution immersion effect of Example 13, a large amount of air is attached to the surface of the stent immersed in the solution (A), and the surface of the stent after immersion is basically not wetted (B);

[0049] Fig.19 Optical microscope photograph of the stent of Example 14 after immersion in the solution;

[0050] Fig. 20 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 16;

[0051] Fig.21 This is a high-magnification SEM image of the cross section of the fiber filaments and coating on the composite material stent prepared in Example 17;

[0052] Fig. 22 It is a bar graph of the test results of the water contact angle on the surface of the stent of Comparative Example 1 and Example 1;

[0053] Fig.23Fluorescence staining photos of live and dead cells after culturing cells on the scaffold prepared in Comparative Example 1 for 3 days; (A) represents live cell staining; (B) represents dead cell staining;

[0054] Fig.24 It is a bar graph of the MTT test results of cells on the scaffolds of Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0056] In order to make up for the defects of using only artificial synthetic materials or natural biological materials, the inventors combined artificial synthetic materials and natural biological materials to construct a composite material scaffold. Specifically, the present invention forms a composite material scaffold with a biologically active surface by coating a layer of natural biological material coating on the surface of the artificial synthetic material 3D printed scaffold. It has better surface activity than pure synthetic material scaffolds and better mechanical properties than pure natural materials.

[0057] The embodiment of the present invention provides a composite material stent, comprising a stent body formed of a synthetic biomaterial, and an active coating formed of a natural biomaterial coated on the stent body. The synthetic biomaterial provides the shape, three-dimensional porous structure and mechanical strength required for the stent, and the active coating formed of the natural biomaterial provides the hydrophilicity and biological activity required for the stent.

[0058] In some embodiments, the synthetic biomaterial is selected from at least one of polycaprolactone, polylactic acid, polyglycolic acid, polytrimethylene carbonate, polylactic acid-glycolic acid copolymer, polylactic acid-caprolactone copolymer and polylactic acid-trimethylene copolymer. The synthetic biomaterial can be any one or more of the above, all of which are suitable for preparing the stent body and have good molding effects.

[0059] In some embodiments, the natural biomaterial is selected from at least one of sodium hyaluronate, chondroitin sulfate, sodium alginate, chitosan, collagen, fibrin, silk protein and gelatin. The natural biomaterial can be any one or more of the above, all of which have good hydrophilicity and biological activity. Specifically, collagen can be type I or type II. Natural biomaterials are roughly divided into two categories: natural polysaccharides and proteins. The following examples select sodium hyaluronate (representing polysaccharides, other polysaccharide materials have similar properties) and collagen (representing proteins, other proteins have similar properties) as representatives for examples, and the results of other similar materials can be inferred.

[0060] In some embodiments, the scaffold body has a three-dimensional through-pore structure, which can better promote cell adhesion and maintain cell differentiation after loading the active coating, thereby achieving a better effect of cartilage repair.

[0061] Furthermore, the stent body can be prepared by a melt extrusion additive manufacturing method, and the melt extruded fiber filaments of the synthetic biomaterial are arranged in parallel at different angles and stacked layer by layer to obtain a pore structure with different shapes of three-dimensional penetration. Among them, the fiber diameter is 200μm-500μm, such as 200μm, 300μm, 400μm, 500μm, etc.; the fiber spacing is 370μm-1000μm, such as 370μm, 450μm, 900μm, 1000μm, etc.; the porosity of the stent body is 65%-83%, such as 65%, 70%, 75%, 80%, 83%, etc. By regulating the fiber diameter, fiber spacing and porosity, it is beneficial to form a uniform active coating on the surface of the stent body, thereby improving the repair effect of the obtained composite material stent. Wire diameter, spacing and porosity are related parameters and cannot take extreme values ​​at the same time. When determining the spacing and porosity, the wire diameter value is fixed, and the wire spacing and porosity are the main variables.

[0062] Furthermore, the thickness of the active coating is 1.0 μm-5.0 μm, such as 1.0 μm, 3.0 μm, 5.0 μm, etc. The mass fraction of the active coating in the composite material scaffold is 1.0%-5.0%, such as 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc. By adjusting the thickness and mass fraction of the active coating, the composite material scaffold has better hydrophilicity and bioactivity.

[0063] The embodiment of the present invention also provides a method for preparing a composite material bracket, which includes coating an active coating on a bracket body to prepare a composite material bracket that meets the above-mentioned embodiment. The steps are as follows:

[0064] S1. Preparation of the stent

[0065] The stent body can be prepared from synthetic biomaterials using existing 3D printing technology, such as continuous melt extrusion additive manufacturing technology.

[0066] The specific material of the synthetic biomaterial is referred to the above content of the specification, and will not be repeated here. The specific operation process of additive manufacturing is not limited, and can refer to the existing technical solutions for preparing scaffolds using synthetic biomaterials, so that the prepared scaffold body meets the requirements of fiber diameter, fiber spacing and porosity.

[0067] S2. Bracket surface treatment

[0068] First, the stent body is immersed in alkaline solution, and the surface is etched with the alkaline solution to obtain a micro-nano structure on the surface of the stent fiber, thereby improving the hydrophilicity of the stent so that the natural material solution can easily infiltrate the stent and form a uniform and stable active coating on the surface of the stent body.

[0069] In some embodiments, the process of obtaining the micro-nano structure includes: immersing the stent body in an alkali solution with a concentration of 1mol / L-10mol / L for surface treatment, the treatment temperature is 25℃-45℃, and the treatment time is 12-24h, so as to form more micro-nano structures on the fiber surface of the stent body, so that the active coating is more tightly combined and distributed more evenly. If the concentration of the alkali solution is too low, there will be too few surface micro-nano structures; if the concentration of the alkali solution is too high, the stent mass will lose too much after surface treatment, and the mechanical properties will decrease.

[0070] Specifically, the concentration of the alkali solution can be 1mol / L, 3mol / L, 5mol / L, 8mol / L, 10mol / L, etc.; the treatment temperature can be 25°C, 25°C, 30°C, 35°C, 45°C, etc.; the treatment time can be 12h, 18h, 24h, etc.

[0071] Furthermore, the alkali solution is selected from at least one of a sodium hydroxide aqueous solution and a potassium hydroxide aqueous solution. The alkali solution may be any one or more of the above, and all of them can form a micro-nano structure on the surface of the stent fiber.

[0072] Furthermore, after soaking in the alkali solution, the treated stent is washed with water and dried. The alkali solution remaining on the surface can be removed by washing with purified water, and then dried in a blast drying oven. The drying temperature can be 35°C-45°C.

[0073] S3. Preparation of stent surface coating

[0074] The stent treated in step S2 is immersed in a natural biomaterial solution to form an active coating. During the immersion process, the natural biomaterial adheres to the surface of the stent to form a uniform coating.

[0075] In some embodiments, the process of forming the active coating includes: immersing the stent body having the micro-nano structure in a natural biomaterial solution, immersing for 10-30 minutes (such as 10 minutes, 20 minutes, 30 minutes, etc.) under vacuum conditions, and then drying, and vacuuming the natural biomaterial so that it can completely penetrate and fill the pore structure of the stent body to form a stable and uniform coating. The types of natural biomaterials can refer to the above content of the specification, and will not be repeated here.

[0076] Furthermore, the mass fraction of the natural biomaterial solution is 0.5%-1.5%, and the operating pressure during the impregnation process is controlled to be -100KPa~0KPa (such as -100KPa, -80KPa, -50KPa, -30KPa, 0KPa, etc.). By regulating the concentration of the solute in the natural biomaterial solution and the vacuum conditions, the natural biomaterial can be better attached to the surface of the stent body to form a uniform coating.

[0077] Specifically, the mass fraction of the natural biomaterial solution can be 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, etc.

[0078] The stent treated in step S2 is immersed in a container filled with a natural biomaterial solution, and the immersion is performed under vacuum. After the immersion is completed, the stent is taken out from the natural biomaterial solution, and the stent is placed on a hydrophobic platform for drying. The drying temperature is controlled to be 30°C-45°C, and the drying time is 12h-72h. In actual operation, after the stent is placed on the hydrophobic platform, it is placed in a constant temperature blast drying oven for drying to obtain a natural biomaterial coating. By using a hydrophobic platform, the coating can be fully coated on the stent fiber filaments to prevent film formation on the bottom surface of the stent. Compared with freeze-drying, the drying method of drying can better coat the stent fiber filaments with a coating to prevent the coating material from filling in the pores.

[0079] Specifically, the hydrophobic platform can be a super-hydrophobic plastic plate, a super-hydrophobic metal plate, a super-hydrophobic glass plate, a polytetrafluoroethylene plate, a non-stick pan, etc. The drying temperature can be 30°C, 35°C, 37°C, 40°C, 45°C, etc.; the drying time can be 12h, 24h, 48h, 72h, etc.

[0080] S4. Preparation of cross-linked coating

[0081] The active coating formed can be a cross-linked coating or a non-cross-linked coating, and step S4 is performed according to the situation.

[0082] When the active coating is a cross-linked coating, the cross-linking method is as follows: place the stent containing the natural biomaterial coating in a cross-linking agent solution, carry out a cross-linking reaction at room temperature (such as 25°C-30°C), and wash and dry after the reaction. The cross-linking agent and solvent on the surface are removed by washing with purified water, and the final composite material stent product is obtained after drying to remove the surface moisture. Specifically, the drying method is not limited, and a blast drying oven can be used for drying, and the drying temperature can be 35°C-45°C.

[0083] In some embodiments, the crosslinking agent used in the crosslinking agent solution is selected from at least one of glutaraldehyde, calcium chloride and EDC / NHS according to the different natural materials, and the crosslinking agent can be any one or more of the above. Among them, EDC / NHS is used in combination, and other crosslinking agents can be used alone. The crosslinking time is 0.5h-24h, such as 0.5h, 1.0h, 5.0h, 10.0h, 15.0h, 20.0h, 24.0h, etc. The concentration of the crosslinking agent in the crosslinking agent solution is not limited, and can be regulated according to the conventional dosage of different crosslinking agents.

[0084] The composite material scaffold provided by the embodiment of the present invention can be used in the preparation of cartilage repair products, and is suitable for a variety of cartilages, such as articular cartilage, nasal cartilage or ear cartilage. The composite material scaffold provided by the embodiment of the present invention has the following advantages: (1) The surface of the scaffold contains abundant active groups, including at least one of hydroxyl, carboxyl or amino groups, and has good biocompatibility and biological activity, which is conducive to interacting with cells, stimulating cells to release active factors, and promoting cell adhesion, proliferation and differentiation; (2) The scaffold has good hydrophilic and water absorption properties, with a water absorption rate of 100-200%, which is conducive to tissue fluid or blood entering the scaffold and providing a physiological environment for cell growth.

[0085] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0086] Example 1

[0087] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0088] (1) Preparation of the stent

[0089] The polycaprolactone particles were added to the printing barrel of the additive manufacturing equipment (equipment model: OPUS Pro36, the same below) for continuous melt micro-extrusion to print the porous stent body. The printed stent body has an outer dimension of 21*21*1mm, a fiber diameter of 200μm, a filament spacing of 450μmm, a triangular pore structure, and a porosity of 69.5%.

[0090] (2) Bracket surface treatment

[0091] The stent body was immersed in a 2 mol / L NaOH solution, and the stent was fully and evenly immersed at 37°C for 24 hours. The stent was then taken out, washed with ultrapure water for 5 times, and dried in a 37°C forced air drying oven.

[0092] The treated scaffold fiber surface has a uniform micro-nano structure (such as Figure 1 shown).

[0093] (3) Preparation of stent surface coating

[0094] The stent body surface-treated in step (2) was immersed in a beaker containing 0.5% sodium hyaluronate solution, and vacuumed for 10 minutes (the pressure was controlled to be -100 KPa, the same below), and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a blast drying oven at 45° C. for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0095] The microstructure of the sodium hyaluronate coating on the stent was tested by scanning electron microscopy. Figure 2 and Figure 3 As shown, it can be seen that the average thickness of the coating is 1.38 μm. By weighing the mass of the stent before and after the surface coating is prepared, the mass fraction of the coating in the stent is calculated to be 1.29%.

[0096] The polycaprolactone scaffold containing sodium hyaluronate coating has good hydrophilicity and biocompatibility. The hydrophilicity test is carried out using a contact angle tester, and the water contact angle is zero (detected using a contact angle tester), and there is no cytotoxicity.

[0097] The growth of cells on the scaffold was tested by cell live and dead staining. The test method was as follows: After 7 days of cell culture, a live and dead cell staining solution was prepared by mixing a 1:1 calcein-AM solution with a PI solution. Then, 100 μL of the staining solution was added to each well and incubated in the dark at 37°C for 30 minutes. Subsequently, images were taken using an inverted fluorescence microscope (Ts2-FL, Nikon, Japan). The test results are shown in Figure 2. Figure 4 As shown, from Figure 4 It can be seen that cells can grow well on the scaffold.

[0098] In vivo experiments were conducted using a rabbit nasal cartilage defect model to verify the cartilage regeneration effect of the scaffold. Alcian blue was used for tissue staining. The results are as follows Figure 5 As shown, 6 months after implantation, new chondrocytes and matrix were formed around and inside the scaffold.

[0099] Example 2

[0100] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0101] (1) Same as Example 1.

[0102] (2) Same as Example 1.

[0103] (3) Preparation of stent surface coating, the specific steps are as follows:

[0104] The surface-treated stent body was immersed in a beaker containing 0.8% sodium hyaluronate solution, and vacuumed for 10 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a blast drying oven at 45°C for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0105] The microstructure of the sodium hyaluronate coating on the stent was tested by scanning electron microscopy. Figure 6 As shown, the average thickness of the coating is 2.34 μm; the coating composition is qualitatively analyzed by energy dispersive spectrometer (EDS), as shown in Figure 7 As shown, a clear sodium hyaluronate coating can be seen. By weighing the mass of the stent before and after the surface coating is prepared, the average mass fraction of the coating in the stent is calculated to be 1.89%.

[0106] Example 3

[0107] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0108] (1) Same as Example 1.

[0109] (2) Same as Example 1.

[0110] (3) Preparation of stent surface coating, the specific steps are as follows:

[0111] The surface-treated stent body was immersed in a beaker containing 1% sodium hyaluronate solution, and vacuumed for 10 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a blast drying oven at 45°C for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0112] The microstructure of the sodium hyaluronate coating on the stent was tested by scanning electron microscopy. Figure 8 As shown, the average thickness of the coating is 3.09 μm. By weighing the mass of the stent before and after the surface coating is prepared, the average mass fraction of the coating in the stent is calculated to be 3.48%.

[0113] Example 4

[0114] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0115] (1) Same as Example 1.

[0116] (2) Same as Example 1.

[0117] (3) Preparation of stent surface coating, the specific steps are as follows:

[0118] The surface-treated stent body was immersed in a beaker containing 1.3% sodium hyaluronate solution, and vacuumed for 10 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a blast drying oven at 45°C for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0119] The microstructure of the sodium hyaluronate coating on the stent was tested by scanning electron microscopy. Fig. 9 As shown, the average thickness of the coating is 3.94 μm. By weighing the mass of the stent before and after the surface coating is prepared, the average mass fraction of the coating in the stent is calculated to be 4.51%.

[0120] Example 5

[0121] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0122] (1) Same as Example 1.

[0123] (2) Same as Example 1.

[0124] (3) Preparation of stent surface coating, the specific steps are as follows:

[0125] The surface-treated stent body was immersed in a beaker containing 1.5% sodium hyaluronate solution, and vacuumed for 10 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a blast drying oven at 45°C for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0126] The microstructure of the sodium hyaluronate coating on the stent was tested by scanning electron microscopy. Fig.10 As shown, the average thickness of the coating is 4.39 μm. By weighing the mass of the stent before and after the surface coating is prepared, the average mass fraction of the coating in the stent is calculated to be 4.78%.

[0127] Example 6

[0128] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0129] (1) Preparation of the stent

[0130] The polycaprolactone particles were added to the printing barrel of the additive manufacturing equipment for continuous melt micro-extrusion to print the porous stent body. The printed stent body has an outer dimension of 21*21*1mm, a fiber diameter of 200μm, a wire spacing of 370μmm, a triangular pore structure, and a porosity of 65%.

[0131] (2) Bracket surface treatment

[0132] The stent body was immersed in 1 mol / L NaOH solution, and the stent was fully and evenly immersed at 25°C for 24 hours. The stent was then washed with ultrapure water for 5 times and dried in a 37°C forced air drying oven.

[0133] The treated scaffold fiber surface has a uniform micro-nano structure (similar to Figure 1 shown).

[0134] (3) Preparation of stent surface coating

[0135] The stent body surface-treated in step (2) was immersed in a beaker containing 0.5% sodium hyaluronate solution, and vacuumed for 30 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a 45° C. forced drying oven for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0136] After testing, the microscopic morphology of the sodium hyaluronate coating on the stent is as follows Fig.11 As shown, the average thickness of the coating is 1.07 μm and the average mass fraction of the coating is 1.03%.

[0137] Example 7

[0138] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0139] (1) Preparation of the stent

[0140] Polycaprolactone particles (commercially available raw material molecular weight of 80,000) were added to the printing barrel of the additive manufacturing equipment for continuous melt micro-extrusion to print the porous stent body. The printed stent body has an outer dimension of 21*21*1mm, a fiber diameter of 200μm, a wire spacing of 1000μmm, a triangular pore structure, and a porosity of 83%.

[0141] (2) Bracket surface treatment

[0142] The stent body was immersed in a centrifuge tube filled with 10 mol / L NaOH solution, and the stent was fully and evenly immersed at 45°C for 6 hours. The stent was then washed with ultrapure water for 5 times and dried in a 37°C forced air drying oven.

[0143] The treated scaffold fiber surface has a uniform micro-nano structure (similar to Figure 1 shown).

[0144] (3) Preparation of stent surface coating

[0145] The stent body surface-treated in step (2) was immersed in a beaker containing a 0.5% sodium hyaluronate solution, and vacuumed for 10 minutes, and then the stent immersed in the sodium hyaluronate solution was placed on a hydrophobic platform. Finally, the hydrophobic platform on which the stent was placed was placed in a 45° C. forced drying oven for 24 hours to obtain a polycaprolactone stent containing an uncross-linked sodium hyaluronate coating.

[0146] After testing, the microscopic morphology of the sodium hyaluronate coating on the stent is as follows Fig.12 As shown, the average thickness of the coating is 2.33 μm and the average mass fraction of the coating is 2.61%.

[0147] Example 8

[0148] The only difference from Example 1 is that in step (3), the hydrophobic platform is replaced by an ordinary glass plate.

[0149] The results showed that the bottom surface of the stent was completely covered with sodium hyaluronate film (such as Fig.13 ), which affected the pore structure of the scaffold and did not form a coating on the fiber filaments.

[0150] Example 9

[0151] The only difference from Example 1 is that the drying in step (3) is replaced by freeze-drying, the freeze-drying temperature is controlled to -60°C, and the freeze-drying time is 24h.

[0152] The results showed that the pores of the stent were filled and blocked by sodium hyaluronate material (e.g. Fig.14 ), which affected the pore structure of the scaffold and did not form a coating on the fiber filaments.

[0153] Example 10

[0154] The only difference from Example 1 is that the concentration of the sodium hyaluronate solution in step (3) is 0.1%.

[0155] The results showed that the coating was unevenly distributed, with only some fibers or local areas of the fibers being covered with the coating (e.g. Fig.15 ), coating preparation failed.

[0156] Embodiment 11

[0157] The only difference from Example 1 is that the concentration of the sodium hyaluronate solution in step (3) is 2.0%.

[0158] The results showed that the solution had poor viscosity and fluidity, the solution immersion process took too long, and many pores of the stent were blocked by the coating (such as Fig.16 ), coating preparation failed.

[0159] Example 12

[0160] The only difference from Example 1 is that the concentration of the sodium hyaluronate solution in step (3) is 3.0%.

[0161] The results showed that the solution had difficulty flowing and it was difficult to infiltrate the stent; the coating thickness was uneven, and most of the pores in the stent were blocked by the coating (e.g. Fig.17 ), coating preparation failed.

[0162] Example 13

[0163] The only difference from Example 1 is that the concentration of the sodium hydroxide solution in step (2) is 0 mol / L.

[0164] The results showed that the scaffold had poor hydrophilicity and it was difficult for natural material solutions to infiltrate the scaffold (e.g. Fig.18 ), resulting in the failure of coating preparation.

[0165] Embodiment 14

[0166] The only difference from Example 1 is that the concentration of the sodium hydroxide solution in step (2) is 0.1 mol / L.

[0167] The results showed that the scaffold had poor hydrophilicity, and it was difficult for the natural material solution to completely infiltrate the scaffold. During the infiltration process, bubbles attached to the scaffold (such as Fig.19 ), resulting in the failure of coating preparation.

[0168] Embodiment 15

[0169] The only difference from Example 1 is that the concentration of the sodium hydroxide solution in step (2) is 15 mol / L.

[0170] The results showed that the mass loss of the stent exceeded 10%, affecting the original mechanical properties of the stent.

[0171] Example 16

[0172] The only difference from Example 1 is that in step (1), polycaprolactone is replaced by polylactic acid (the molecular weight of the commercially available raw material is 100,000).

[0173] The results showed that the prepared polylactic acid scaffold contained a sodium hyaluronate coating, e.g. Fig. 20 As shown, the average thickness of the coating is 1.35 μm and the mass fraction is 1.17%.

[0174] Embodiment 17

[0175] The only difference from Example 1 is that in step (3), the sodium hyaluronate solution is replaced by a collagen type I solution of equal concentration, and the drying temperature is changed to 30°C.

[0176] The results showed that the average thickness of the collagen coating was 1.23 μm, and the microscopic morphology of the collagen coating on the scaffold was as follows: Fig.21As shown, the average mass fraction of the collagen coating was 1.05%.

[0177] Embodiment 18

[0178] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0179] (1) Same as Example 1.

[0180] (2) Same as Example 1.

[0181] (3) Same as Example 1.

[0182] (4) Cross-linking of the stent surface coating, the specific steps are as follows:

[0183] The stent with sodium hyaluronate coating was immersed in 90% anhydrous ethanol / 50mM EDC / 20mM NHS solution, cross-linked at room temperature (about 25°C, the same below) for 24 hours, washed with water 5 times after cross-linking, each time for 5 minutes, and then the cross-linked stent was placed in a 37°C constant temperature blast drying oven for 24 hours to obtain a polycaprolactone stent with a cross-linked sodium hyaluronate coating. Among them, "90% anhydrous ethanol / 50mM EDC / 20mM NHS solution" means that 90% anhydrous ethanol is used as the solvent, the EDC concentration is 50mM, the NHS concentration is 20mM, and the anhydrous ethanol concentration is 90%.

[0184] Embodiment 19

[0185] This embodiment provides a method for preparing a composite material bracket, the steps are as follows:

[0186] (1) Same as Example 1.

[0187] (2) Same as Example 1.

[0188] (3) Same as Example 1.

[0189] (4) Cross-linking of the stent surface coating, the specific steps are as follows:

[0190] The polycaprolactone scaffold with type I collagen coating was immersed in 90% anhydrous ethanol / 0.1% glutaraldehyde solution and cross-linked at room temperature for 1 hour. After cross-linking, it was washed with water 5 times, each time for 5 minutes, and then the cross-linked scaffold was placed in a constant temperature forced air drying oven at 30°C for 24 hours to obtain a polycaprolactone scaffold with a cross-linked type I collagen coating.

[0191] Comparative Example 1

[0192] The only difference from Example 1 is that steps (2) and (3) are not performed.

[0193] The results show that the water contact angle of the stent surface in Example 1 is lower than that in Comparative Example 1 ( Fig. 22 ), indicating that the stent with sodium hyaluronate coating has better hydrophilicity. The growth of cells on the stent was tested by live and dead cell staining. The staining photos are shown in Fig.23 The cell proliferation was detected by MTT test. The MTT test results compared with those in Example 1 are shown in Fig.24 As shown, the results show that the MTT test OD value of Comparative Example 1 is lower than that of Comparative Example 1. Figure 4 , Fig.23 and Fig.24 It can be seen that the cell growth condition of Comparative Example 1 is significantly worse than that of Example 1.

[0194] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite material bracket, characterized in that: The invention comprises a stent body formed of synthetic biological material, and an active coating formed of natural biological material is coated on the stent body.

2. The composite material bracket according to claim 1, characterized in that: The synthetic biomaterial is selected from at least one of polycaprolactone, polylactic acid, polyglycolic acid, polytrimethylene carbonate, polylactic acid-glycolic acid copolymer, polylactic acid-caprolactone copolymer and polylactic acid-trimethylene copolymer; And / or, the natural biomaterial is selected from at least one of sodium hyaluronate, chondroitin sulfate, sodium alginate, chitosan, collagen, fibrin, silk fibroin and gelatin.

3. The composite material bracket according to claim 1 or 2, characterized in that: The stent body has a three-dimensional through-pore structure; Preferably, the stent body is prepared by a melt extrusion additive manufacturing method, and is composed of melt-extruded fiber filaments of synthetic biomaterials arranged in parallel and stacked layer by layer at different angles; wherein the fiber filament spacing is 370μm-1000μm, the fiber filament diameter is 200μm-500μm, and the porosity of the stent body is 65%-83%.

4. The composite material bracket according to claim 1 or 2, characterized in that: The thickness of the active coating is 1.0 μm-5.0 μm, and the mass fraction of the active coating in the composite material bracket is 1.0%-5.0%.

5. A method for preparing the composite material bracket according to any one of claims 1 to 4, characterized in that: include: The active coating is coated on the stent body.

6. The preparation method according to claim 5, characterized in that: include: The stent body is firstly immersed in alkaline solution to obtain a micro-nano structure, and then immersed in a natural biological material solution to form the active coating.

7. The preparation method according to claim 6, characterized in that: The process of obtaining the micro-nano structure includes: immersing the stent body in an alkali solution with a concentration of 1 mol / L-10 mol / L for surface treatment, the treatment temperature is 25°C-45°C, and the treatment time is 12h-24h; Preferably, the alkali solution is selected from at least one of a sodium hydroxide aqueous solution and a potassium hydroxide aqueous solution; Preferably, after soaking in the alkaline solution, the treated stent is washed with water and dried.

8. The preparation method according to claim 6, characterized in that: The process of forming the active coating comprises: dipping the stent body having the micro-nano structure into the natural biomaterial solution under vacuum conditions for 10-30 minutes, and then drying; Preferably, the mass fraction of the natural biological material solution is 0.5%-1.5%, and the operating pressure during the immersion process is controlled to be -100KPa~0KPa; Preferably, after the immersion in the natural biomaterial solution is completed, the stent is placed on a hydrophobic platform for drying, and the drying temperature is controlled to be 30° C.-45° C., and the drying time is 12 h-72 h.

9. The preparation method according to claim 8, characterized in that: The process of forming the active coating further includes: after immersing in the natural biomaterial solution and drying, placing the stent containing the natural biomaterial coating in a crosslinking agent solution for a crosslinking reaction, and washing and drying after the reaction; Preferably, the cross-linking agent used in the cross-linking agent solution is selected from at least one of glutaraldehyde, calcium chloride and EDC / NHS according to different natural materials.

10. Use of the composite material scaffold according to any one of claims 1 to 4 or the composite material scaffold prepared by the preparation method according to any one of claims 5 to 9 in the preparation of cartilage repair products; Preferably, the cartilage is selected from at least one of articular cartilage, nasal cartilage and ear cartilage.

Citation Information

Cited By

  • Coating-modified high-molecular polymer porous scaffold as well as preparation method and application thereof

    CN121177574A